Development of a Web-Based Vehicle Monitoring and Reporting Information System to Support Logistics Operations at PT. Shopee Express’s Ngaliyan Branch - Zulvano Ardiansyah Widodo; Budi Hartono; Arsito Ari Kuncoro (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to design and develop a Web-Based Vehicle Monitoring and Reporting Information System to support logistics operations at PT. Shopee Express Ngaliyan Branch. The main problem addressed in this research is the manual vehicle monitoring and travel reporting process, which may cause information delays, inaccurate data, and ineffective fleet supervision. This study applies a software engineering approach using the Waterfall system development method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed as a web-based platform supported by a MySQL database and integrated with Google Maps API to display vehicle positions in real time. The results show that the developed system assists administrators in monitoring vehicle locations, managing driver and vehicle data, viewing travel histories, and generating operational reports automatically. In addition, drivers are able to update travel status, send location data, input travel reports, and upload delivery evidence through the system. System testing using Black Box Testing and User Acceptance Test indicates that the main features operate properly according to user needs. This system contributes to improving operational efficiency, data accuracy, driver performance transparency, and integrated fleet supervision. Therefore, the proposed system can serve as a practical digital solution for supporting logistics management and vehicle monitoring activities.